Mineralogy and Geochemistry of Al-Na'ma area Sand Dunes, Southeastern Tikrit, Northern Iraq - Taha, Taher M.; Mohammed, Amaar J.; Rasheed, Riyad M. (Iraqi Journal of Science, 2024)
Surface sediment characters and understanding the earth's surface processes are very interesting global research topics. The region in southeastern Tikrit city is characterized by the spread of large surface sediment from aeolian deposited types and dunes. These dunes were investigated to understand the origin of these dunes. For this purpose, grain size analysis, XRD, XRF, and heavy mineral analyses were conducted. Results indicate that these sand dunes in the study area are mainly composed of coarse particles such as sand (especially fine sand) with a percentage more than fine particles (mud), and the fine sand fraction is the predominant class. The sand grains are characterized by also negative value of skewness (strongly coarse skewed), moderately sorted, and leptokurtic. The normal distribution curve shows a unimodal type for most samples, reflecting one potential sediment source.Mineralogically, quartz is the main mineral composition of this sand, in addition to other minerals such as feldspar, clay minerals, calcite, dolomite, and gypsum. The identified heavy minerals in these samples were tourmaline, garnet, zircon, kyanite, chlorite, rutile, hornblende, and olivine. Regarding the geochemistry, the distribution of major oxides and trace elements in these samples area showed high SiO2 and TiO2 and low content of Na2O. UCC-normalization reveals enrichment of CaO, Cr, and Cl and depletion of other trace elements.